Peran publik relation dalam membangun hubungan jangka panjang terhadap nasabah bank Syariah - umam, reza khoirul (Maliki Interdisciplinary Journal, 2025)
Public relations (PR) has an important role in building and maintaining long-term relationships with sharia bank customers. In the context of sharia banking, a harmonious relationship between banks and customers is very crucial because sharia banks not only prioritize financial aspects, but also aspects of trust and compliance with sharia principles. PR is responsible for creating a positive image of sharia banks through various effective communication strategies, both internally and externally. One of the main roles of PR is to build customer trust by providing information that is clear, transparent and in accordance with sharia values. PR also plays a role in delivering programs that are relevant to customer needs, such as education about sharia products which is expected to increase customer loyalty. Apart from that, PR also functions as a communication bridge between the bank and customers, ensuring that any feedback or complaints from customers can be received and handled properly. A well-established relationship between PR and sharia bank customers can increase customer satisfaction and loyalty, which ultimately has a positive impact on the sustainability of the bank's business. In the long term, the role of PR in building a good reputation is very important to support the growth of Islamic banks. PR must be able to maintain consistent relationships with customers through continuous communication, so as to create mutually beneficial relationships and in accordance with sharia principles.